Meningkatkan Keterampilan Menyetrika Pakaian bagi Peserta Didik Disabilitas Intelektual Melalui Teknik Modeling (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to evaluate the effectiveness of modeling techniques in improving ironing skills in students with mild intellectual disabilities. This study used a quantitative approach with the Single Subject Research method with an A-B design, where the ability to iron school clothes in baseline conditions (A1) was measured three times and showed the same results, namely 55%. Data analysis showed a stability range of 8, an average value of 55, with an upper limit of 59 and a lower limit of 51, and stability reaching 100%. In the intervention condition (B), which was carried out for eight sessions, the scores obtained by student G were 61%, 72%, 78%, 78%, 83%, 86%, 86%, and 86%. The stability range in this phase was 13, with an average value of 79, an upper limit of 86, a lower limit of 72, and a stability level of 88%. The findings of this study indicate an increase in ironing skills after the implementation of the modeling technique, which means that the technique has proven effective in improving the ability to iron school clothes.